2018
DOI: 10.1177/1753944718781295
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of body mass index on warfarin requirements in hospitalized patients

Abstract: Based on the results of this study, morbidly obese patients may require higher TWD to obtain and maintain a therapeutic INR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In a recent study reviewing warfarin dosing in patients stratified by BMI, participants with a high BMI, particularly more than 40 kg/m 2 had significantly higher warfarin requirements. [ 74 ] A higher weekly dose of warfarin may have implications for time to discharge if the drug is commenced in hospital or in maintaining time in therapeutic range. It would seem that the use of direct oral anticoagulants (DOACs) including dabigatran, apixaban, rivaroxaban and edoxaban for thromboembolism prophylaxis would address this issue.…”
Section: Management Of Af In Obese Patientsmentioning
confidence: 99%
“…In a recent study reviewing warfarin dosing in patients stratified by BMI, participants with a high BMI, particularly more than 40 kg/m 2 had significantly higher warfarin requirements. [ 74 ] A higher weekly dose of warfarin may have implications for time to discharge if the drug is commenced in hospital or in maintaining time in therapeutic range. It would seem that the use of direct oral anticoagulants (DOACs) including dabigatran, apixaban, rivaroxaban and edoxaban for thromboembolism prophylaxis would address this issue.…”
Section: Management Of Af In Obese Patientsmentioning
confidence: 99%
“…For example, Routledge et al [19] identified one of the key factors affecting on warfarin therapy is body weight. Tellor [20] showed morbidly obese patients required higher total weekly dose to maintain a therapeutic INR. Wallace et al [21] compared average warfarin dose with the different patients BMI to get the therapeutic INR in hospital, and found warfarin response dose was decreasing with the BMI increment.…”
Section: Introductionmentioning
confidence: 99%
“…The third patient who also experienced hematuria had an INR value below the therapeutic target on the second and third day with 0.91 and 1.02 INR, respectively. Data limitations of patient characteristics in this study, including BMI which is known to have a higher requirement of warfarin weekly dose to reach the therapeutic target of INR (Tellor et al, 2018), remain unknown. Even though the patient has not reached INR therapeutic target with a likely risk of thromboembolism, the patient experienced bleeding on the fifth and ninth day.…”
Section: Resultsmentioning
confidence: 99%